Lovingkindness : the revolutionary art of happiness - Salzberg, Sharon (Colorado, Shambhala publications, 2020)
Throughout our lives we long to love ourselves more deeply and find a greater sense of connection with others. Our fear of intimacy--both with others and with ourselves--creates feelings of pain and longing. But these feelings can also awaken in us the desire for freedom and the willingness to take up the spiritual path. In this inspiring book, Sharon Salzberg, one of America's leading spiritual teachers, shows us how the Buddhist path of lovingkindness can help us discover the radiant, joyful heart within each of us. This practice of lovingkindness is revolutionary because it has the power to radically change our lives, helping us cultivate true happiness in ourselves and genuine compassion for others. The Buddha described the nature of such a spiritual path as "the liberation of the heart, which is love." The author draws on simple Buddhist teachings,wisdom stories from various traditions, guided meditation practices, and her own experience from twenty-five years of practice and teaching to illustrate how each one of us can cultivate love, compassion, joy, and equanimity--the four "heavenly abodes" of traditional Buddhism.
Foreward / by Jon Kabat-Zinn -- Acknowledgments -- Introduction -- The revolutionary art of happiness -- Relearning loveliness -- Facets of lovingkindness -- Hindrances to lovingkindness -- Working with anger and aversion -- Breaking open the loving heart -- Developing the compassionate heart -- Liberating the mind through sympathetic joy -- The gift of equanimity -- The power of generosity -- Living our love -- Afterword to the 25th anniversary edition -- For more information -- Credits -- About the author.
Keywords: Meditation -- Buddhism; Compassion -- Religious aspects -- Buddhism; Compassion -- Religious aspects -- Buddhism; Meditation -- Buddhism